That eminent tribunal : judicial supremacy and the constitution - Wolfe, Christopher (New forum books., 2004)
The role of the United States Supreme Court has been deeply controversial throughout American history. Should the Court undertake the task of guarding a wide variety of controversial and often unenumerated rights? Or should it confine itself to enforcing specific constitutional provisions, leaving other issues (even those of rights) to the democratic process?